THE IMPACT OF CAPITAL STRUCTURE ON THE ENTERPRISE FINANCIAL STABILITY - Ivanyshcheva, A. V. (Science and Transport Progress, 2009)
Functioning of production enterprises in the conditions of continuous change of market environment require a special attention of management system to providing their activities. The enterprise financial stability management is one of integral parts of the management system. The increased or insufficient financial stability adversely affects the enterprise competition ability that leads to decreasing the profitability and worsening the financial results of its activities.